Identifying Common Genetic Risk Factors of Diabetic Neuropathies - Witzel, Ini-Isabée; Jelinek, Herbert F.; Khalaf, Kinda; Lee, Sungmun; Khandoker, Ahsan H.; Alsafar, Habiba (Frontiers in Endocrinology, 2015)
Type 2 diabetes mellitus (T2DM) is a global public health problem of epidemic proportions, with 60-70% of affected individuals suffering from associated neurovascular complications that act on multiple organ systems. The most common and clinically significant neuropathies of T2DM include uremic neuropathy, peripheral neuropathy, and cardiac autonomic neuropathy. These conditions seriously impact an individual’s quality of life and significantly increase the risk of morbidity and mortality. Although advances in gene sequencing technologies have identified several genetic variants that may regulate the development and progression of T2DM, little is known about whether or not and how these genetic variants are associated with diabetic neuropathy. Significant missing heritability data and complex disease etiologies remain to be explained. This article is the first to provide a review of the genetic risk variants implicated in the diabetic neuropathies, to highlight potential commonalities. We thereby aim to contribute to the creation of a genetic-metabolic model that will help elucidate the cause of diabetic neuropathies, evaluate a patient’s risk profile, and ultimately facilitate preventative and targeted treatment for the individual.